Facile synthesis of cauliflower-like hydrophobically modified polyacrylamide nanospheres by aerosol-photopolymerization. (October 2016) - Shaban, M.; Ramazani S.A, A.; Ahadian, M.M.; Tamsilian, Y.; Weber, A.P.
Graphical Abstract: Highlights: Amphiphilic copolymers were synthesized by the facile method of aerosol-photopolymerization. Polymer particles were produced within the average residence time of 30 s in the photoreactor. Particle size and morphology of polymer nanoparticles were controlled. Photopolymerization was applied at room temperature. Directly solvent-free dry polymer powders with a high purity were obtained. Abstract: Amphiphilic copolymers consist of hydrophilic and hydrophobic monomer units have attracted great technological attention recently, owing to their unique properties and their ability to stabilize various interfaces in aqueous systems. This paper presents a novel and facile approach to produce spherical polyacrylamide, polystyrene and hydrophobically modified polyacrylamide (HM-PAM), as one of the most important type of amphiphilic copolymers, using a continuous aerosol-photopolymerization for the first time. To this end, the monomer droplets were generated by an atomizer, then photopolymerization was initiated ''in flight'' by ultraviolet (UV) irradiation of the aerosol monomer droplets containing photoinitiator within the average aerosol residence time of 30 s in the photoreactor. To control the aqueous solubility, size and morphology of the resulting HM-PAM copolymers, different styrene/acrylamide monomer concentrations were introduced to the system. The textural properties of the obtained materials were characterized by TEM, SEM and N2 adsorption-desorption isotherms. The results revealed that the copolymers and polyacrylamide have cauliflower-like morphologies, while polystyrene has a nearly smooth morphology. Moreover, chemical compositions of the obtained materials were investigated by several characterization techniques such as 1 H NMR, FT-IR, TGA and elemental analysis. 1 H NMR and elemental analysis of resulting copolymers microstructures displayed successful incorporation of styrene in copolymer with a good agreement compared to initial ratios. The production of amphiphilic copolymer of acrylamide and styrene using the facile aerosol-photopolymerization method might open new avenues to produce various amphiphilic copolymers with a variety of hydrophobic and hydrophilic monomers with desirable properties.